Bezel free design of organic light emitting diode display via a‐InGaZnO gate driver circuit integration within active array. Issue 8 (15th July 2019) - Kim, Kyung Min; Han, Inhyo; Noh, Seok; Jang, Young In; Oh, Kilhwan; Kim, Bumsik; Kang, In‐Byeong
Abstract: In this article, we described an innovative design technology of active matrix organic light emitting diode (AMOLED) display, to provide a bezel free design. We designed gate driver circuit of amorphous indium‐gallium‐zinc oxide thin‐film transistors (TFTs) not on the bezel area but within the active array. Although we applied challengeable design, no degradation of electrical/optical properties of panel was observed. Because we effectively prevented capacitive coupling and interference between the emission circuit and integrated gate driver circuit in active array, finally, we successfully demonstrated a bezel free designed AMOLED display of 18.3″ HD (1366 × 768) driven by a‐InGaZnO TFTs. Abstract : In this article, we have proposed and investigated bezel free design of OLED display, showing infinite boarder between the display and environment, through the gate driver integration within active array (GIA). Also, we have successfully demonstrated bezel free designed OLED display of 18.3‐inch HD (85PPI), composed of the gate driver integrated pixel design driven by a‐InGaZnO backplane.